Jamaica 2011 special report (Caribbean Investment Profiles Limited LondonGB, 2011)
Includes articles on and statements by the current and former Prime Ministers of Jamaica, Government Ministers and other prominent Jamaica personalities in all areas of society in Jamaica and in the diaspora. Includes items on other prominent personalities who have made a name for themselves in Jamaica.
Keywords: JAMAICA